2021
DOI: 10.1186/s41231-021-00082-5
|View full text |Cite
|
Sign up to set email alerts
|

Statins in patients with COVID-19: a retrospective cohort study in Iranian COVID-19 patients

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has profoundly affected the lives of millions of people. To date, there is no approved vaccine or specific drug to prevent or treat COVID-19, while the infection is globally spreading at an alarming rate. Because the development of effective vaccines or novel drugs could take several months (if not years), repurposing existing drugs is considered a more ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 81 publications
1
45
1
Order By: Relevance
“…Regarding the latter, the most commonly reported included: (i) Demographics: age, gender, body mass index; (ii) Comorbidities: hypertension, diabetes, coronary heart disease; (iii) Medications: angiotensin converting enzyme inhibitors or angiotensin II receptor blockers, antiplatelets, anticoagulants; (iv) Biochemical indices: lipids, creatinine levels. Some of the studies reported the duration of the follow-up, which ranged from a few days to several weeks [ 20 , 21 , [23] , [24] , [25] , [26] , 28 , 32 , 33 , 41 ]. In addition, 2 studies reported that the median length of hospitalization of the non-survivors was about 10 days [ 27 , 31 ], and 1 study reported that the majority of deaths occurred within the first 2 weeks of follow-up [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the latter, the most commonly reported included: (i) Demographics: age, gender, body mass index; (ii) Comorbidities: hypertension, diabetes, coronary heart disease; (iii) Medications: angiotensin converting enzyme inhibitors or angiotensin II receptor blockers, antiplatelets, anticoagulants; (iv) Biochemical indices: lipids, creatinine levels. Some of the studies reported the duration of the follow-up, which ranged from a few days to several weeks [ 20 , 21 , [23] , [24] , [25] , [26] , 28 , 32 , 33 , 41 ]. In addition, 2 studies reported that the median length of hospitalization of the non-survivors was about 10 days [ 27 , 31 ], and 1 study reported that the majority of deaths occurred within the first 2 weeks of follow-up [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies (n = 41,807, weighted age 56 ± 8 years, men 51%, hypertension 34%, diabetes 21%, coronary heart disease 11%, statin users 14%) reported the adjusted hazard ratio for death in statin users versus non-users [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. The pooled estimate of hazard ratio was 0.65 (95% confidence intervals [CI] 0.53, 0.81) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since December 2019, COVID-19 has been a resident of the world. Early efforts ranged from the development of diagnostic assays [80][81][82][83] and specific therapeutics [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] to optimizing health monitoring [103,104]. Despite this effort, in addition to our knowledge and experience from the recent outbreaks [105], it mainly relied on non-pharmacological interventions to control the pandemic, e.g., quarantine and social isolation [106,107].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study conducted in Iranian COVID-19 patients highlighted that statins (40 mg daily) might reduce mortality in COVID-19 patients and improve lung function. They showed that using statins long-term before exposure to infection might be most effective therapeutically by controlling cytokine storm, targeting the autophagy pathway, mediating ACE2 expression, and decreasing lung scar formation in COVID-19 patients [150].…”
Section: Antivirals Targeting Autophagymentioning
confidence: 99%